Illness cognitions and health behaviours in adult asthmatics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Laird, Richard John (Massey University, 1995)
A study in the area of health psychology, focusing on illness cognitions and health behaviours and employing a cognitive approach, was conducted. The aim of the study was to test two theoretical models of the determinants and consequences of perceived seriousness of illness using adult asthmatics and, supplementary to this, to generate some information of practical value in self-managing this illness. It was hypothesized that perceived prevalence, perceived treatability, and asthma history (duration, average intensity over entire history, average intensity over the last six months, and frequency of attacks) would correlate with perceived seriousness (self-rated seriousness and number and frequency of symptoms), and that these relationships would be moderated by repressive defence style. It was further hypothesized that seriousness would influence asthma health behaviour (competencies and adherence), and that response and personal efficacies would moderate these relationships. These hypotheses were tested using data from two mail surveys of members of New Zealand regional Asthma Societies, conducted six months apart (N=412 and 389 respectively). The results revealed limited support for the model examining determinants. Only average intensity over entire history, average intensity over the last six months, and frequency of attacks were positively related to self-rated seriousness, whilst average intensity over entire history was positively related to number and frequency of symptoms. There was no evidence that repressive defence style moderated any of the seriousness relationships. However, repressive defence style related to number and frequency of symptoms, but not to self-rated seriousness. The findings provide some support for the notion that rational information processing dominates the seriousness relationships in persons with chronic asthma. The desensitizing influence of asthmatics' experiences with, and knowledge of, asthma was offered as an explanation for the null relationships between duration and seriousness, prevalence and seriousness, and treatability and seriousness. The findings also revealed limited support for the consequences model. Only one seriousness-health behaviour relationship emerged, such that number of symptoms positively related to health competencies. This finding is consistent with a number of studies reporting that the experience of symptoms motivates health behaviour. The competing influences of seriousness as a motivator of health behaviour versus the tendency for seriousness to be negatively related to adherence to complex regimens was offered as a possible explanation for the null relationship between seriousness and adherence. Self-efficacy was not a moderator of the seriousness-health behaviour relationships. It was concluded that methodological inadequacies may have contributed to this result. Despite the general lack of support for the models, the study led to some interesting discussion on a range of largely theoretical issues. For example, it was concluded that an assertion made early in the study that seriousness is a salient illness cognition may not be justified. Additionally, the study findings have three potential applications in the area of asthma self-management. First, the percentage of asthmatics using each of the health competencies provides information of use to asthma educators and clinicians in targeting asthmatics weak in particular areas of self-management. Second, variations identified in the adherence practices and use of health competencies by age, gender, educational level, and number of symptoms should also be useful to asthma professionals, for the same reason. Third, of all the study variables, response efficacy was identified as being most important in determining asthma health behaviour. It is suggested that developers of asthma self-management programmes should incorporate this variable in programmes aimed at promoting health behaviours.
Keywords: Asthma; Asthmatics; Psychology; Clinical health psychology